Financial Sector Assessment Program : Nigeria - Crisis Management and Crisis Preparedness Frameworks - International Monetary Fund (World Bank, Washington, DC, 2013)
This note elaborates on the recommendations made in the Financial Sector Assessment Program (FSAP) for Nigeria in the areas of contingency planning, crisis management, and bank resolution. It summarizes the findings of the FSAP mission undertaken during September 4 to 19, 2012 and is based upon analysis of the relevant legal and policy documents and extensive discussions with the authorities and private sector representatives. The Nigerian financial system experienced a banking crisis in 2008-2009, partly triggered by the global financial crisis and by domestic events. The decisive crisis response effectively stabilized the banking system, but the challenge now is to devise a credible exit strategy and to strengthen the resolution framework. This note is structured as follows: chapter one sets out an overview of the banking crisis of 2009; chapter two analyses the institutional framework and coordination arrangements for systemic risk monitoring, crisis management, and cross-border coordination; chapter three assesses the approaches to intervene with potential problem institutions at an early stage; chapter four covers crisis management tools including official financial support, the resolution framework, Asset Management Corporation of Nigeria (AMCON); chapter five reviews the deposit insurance framework; and chapter six addresses the issue of legal protection.